Relasi Antara Ritual Lobo Keda Dan Pola Permukiman Adat Di Desa Nggela Kabupaten Ende - Kerong, Fabiola T. A.; Kurniawan, DVX. Deddy; Toy, Melky (Program Studi Teknik Sipil dan Program Studi Arsitektur Fakultas Sains & Teknologi Universitas Flores, 2023)
The Lobo Keda ritual is an inauguration of Sao Keda (which is a meeting place) for Mosalaki, traditional leaders of the traditional settlement in Nggela Village. There are seventeen Mosalaki inhabiting 15 traditional houses who continuously maintain their unique indigenous culture. This primary study aims to look at a Lobo Keda ritual process by observing community behaviour and a relationship between Mosalaki and traditional settlement patterns. The research was conducted by qualitative descriptive research method. The results reveal data on how the Lobo Keda ritual and traditional settlement patterns in Ngela Village influences one another, as well as explain how other factors may be influencing such as history, beliefs, cosmology, orientation, sacred elements and social structure.